1981
DOI: 10.1136/bmj.282.6269.1023
|View full text |Cite
|
Sign up to set email alerts
|

Familial hypocalciuric hypercalcaemia and acute pancreatitis.

Abstract: Four families with familial hypocalciuric hypercalcaemia were studied. The probands presented with abdominal pain, which in three was due to acute pancreatitis; in two the condition was life threatening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0
1

Year Published

1983
1983
2004
2004

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(44 citation statements)
references
References 14 publications
5
38
0
1
Order By: Relevance
“…With respect to clinical correlates of hepatic expression of the CASR, they found a higher incidence of FHH-affected family members with gall stones than in the general population. Some reports (55)(56)(57) have suggested that FHH can be associated with recurrent pancreatitis. Pancreatitis is most often secondary to alcoholism or biliary tract disease and less often to other causes including hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to clinical correlates of hepatic expression of the CASR, they found a higher incidence of FHH-affected family members with gall stones than in the general population. Some reports (55)(56)(57) have suggested that FHH can be associated with recurrent pancreatitis. Pancreatitis is most often secondary to alcoholism or biliary tract disease and less often to other causes including hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…The extra measured parameter, serum calcium, rarely exceeds 3.2 mmol/L in FBHH. 1,6,7,9,12,13,18,29,43 In two early extensive reviews, 3,15 occasional values up to 3.5 mmol/L were reported. Therefore, serum calcium may have higher values in PHPT than in FBHH 6,7 and result in a lower calcium:creatinine clearance ratio in some cases, and thus a greater overlap in results.…”
Section: Laboratory Features Of Fbhhmentioning
confidence: 99%
“…The numbers of subjects from each study, with the range and median of the six most commonly studied biochemical parameters overall, are summarized in Table 3. Of the 10 studies, three were of a single large kindred, 1,13,18 ¢ve consisted of series of cases of FBHH and PHPT collected separately over unspeci¢ed time periods, 3,9,12,42,43 and two were prospective studies of unselected cases of hypercalcaemia over a 3-year period in the same hospital. 6,7 A spreadsheet containing the original data from these studies is available at www.acb.org.uk/annclinbiochem/ webwise/ADHHClinBiochem.xls and www.acb.org.uk/ annclinbiochem/webwise/FBHHCalciumdata.xls Table 4 summarizes data for the six most commonly measured biochemical parameters.…”
Section: Laboratory Features Of Fbhhmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical experience of FHH is limited, but there is general agreement that with few exceptions the condition is benign. Some patients have presented with acute pancreatitis which has endangered life (Davies et al 1981). The role of parathyroid hor¬ mone in the pathogenesis of FHH is uncertain; immunoassayable parathyroid hormone (iPTH) can often be detected in the serum, sometimes in increased amounts.…”
mentioning
confidence: 99%